Laser treatments of Nimonic 263 nickel-based superalloy - Dubravka Milovanović; Anđelka Milosavljević; Željko Radovanović; Radomir Jovičić (Zaštita Materijala)
In this paper, the influence of parameters of laser processing (drilling, cutting, welding and laser shock peening) on microstructure of superalloy Nimonic 263 are investigated. Drilling and welding process are carried out on the Nd: YAG laser model LS-HTS Mobile P160. When drilling the holes, the parameters of pulse frequency (5 Hz, 7 Hz and 9 Hz) and the pulses duration (1.8 ms to 3.6 ms) are varied. The microstructure is investigated and geometrical and metallurgical characteristics of the holes are determined.Cutting is carried out on the laser BISTRONIC, (2000), BISTAR 3015. The parameters that were varied are as follows: the average laser power, laser velocity, the pressure of the assisting gas and the focus position. Based on the geometrical characteristics of the cuts and surface morphology the optimal parameters are discussed and defined. The laser welded joints of Nimonic 263, in addition to microscopic examination and surface profilometry, were subjected to the destructive testing. During the laser shock peening, the samples were exposed to laser light at a wavelength of 1064 nm and 532 nm, with the number of accumulated pulses 50, 100 and 200. The operating laser was Nd: YAG EKSPLO, SL212P model. Structural analysis of Nimonic 263 was carried out using light microscopy, scanning electron microscopy and EDS analysis. Microhardness measurements were carried out using the Vickers method under load of 9,81N. Profilometry was performed on a contactless profilometer Zygo Newview 7100.